2009
DOI: 10.1371/journal.pone.0006981
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Characterizing a Novel Protein Kinase STK35L1 and Deciphering Its Orthologs and Close-Homologs in Vertebrates

Abstract: BackgroundThe human kinome containing 478 eukaryotic protein kinases has over 100 uncharacterized kinases with unknown substrates and biological functions. The Ser/Thr kinase 35 (STK35, Clik1) is a member of the NKF 4 (New Kinase Family 4 ) in the kinome with unknown substrates and biological functions. Various high throughput studies indicate that STK35 could be involved in various human diseases such as colorectal cancer and malaria.Methodology/Principal FindingsIn this study, we found that the previously pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…We found that the mutant EGFP-STK35L1Δ1-133 (aa 1–133 were deleted) was excluded from the nucleolus but mainly localized in the nucleus (Figure 1C). This mutant corresponds to the protein previously described as STK35 [18]. Our data indicate that the N-terminal aa 1–133 contains a functional nucleolar localization signal (NoLS) in STK35L1 that is absent in STK35.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…We found that the mutant EGFP-STK35L1Δ1-133 (aa 1–133 were deleted) was excluded from the nucleolus but mainly localized in the nucleus (Figure 1C). This mutant corresponds to the protein previously described as STK35 [18]. Our data indicate that the N-terminal aa 1–133 contains a functional nucleolar localization signal (NoLS) in STK35L1 that is absent in STK35.…”
Section: Resultssupporting
confidence: 53%
“…We have previously shown that STK35L1 is mainly localized in the nucleolus and the nucleus [18]. To predict a functional nuclear localization signal (NLS) in STK35L1, the basic amino acid-rich motifs of STK35L1 were analyzed by manual comparison with known NLSs of different proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-length STK35L1 was obtained using a multistep cloning strategy as previously described (Goyal et al, 2009). Primers were 5 0 -GACAGATCTATGGGCCACCAGGAGTCTCC-3 0 (F-1), 5 0 -GGGC CTCGGCCGCCACCGGATC-3 0 (R-520), 5 0 -ATGGAAACGGGGAAGGAC GGCGCCCGC-3 0 (F-400) and 5 0 -CAAGTCGACTTAAGCAGCACATGTG ACCTG-3 0 (R-1605).…”
Section: Constructsmentioning
confidence: 99%
“…Serine/threonine kinase 35 (STK35) is a member of the serine/threonine protein kinase family [9]. A few studies have investigated the biological function of STK35.…”
Section: Introductionmentioning
confidence: 99%